Model Perancangan Kawasan Wisata Musik di Kota Ambon Dengan Pendekatan Arsitektur Simbiosis - Matias Sabono; Noviar Nurdin Kasim; Faizah Mastutie (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2022)
Ambon City is the center of the port, tourism, and education in the Maluku archipelago. Ambon City and music cannot be separated, even music has become the core movement of the city known as Ambon Manise because musical intuition is naturally inherent in Ambonese life. The development of music in the city of Ambon is very fast, Ambon is a city that has a lot of music enthusiasts, and has even become one of the cities that produce famous music artists in Indonesia. In the mid-20th century, Ambon produced famous singers from national to international levels. This makes Ambon city chosen by UNESCO as one of the world's creative music cities. In developing Ambon City as a world music city, the Ambon City government has prepared 25 plans which are divided into five pillars, namely musicians and communities, infrastructure, education, industrial development, and socio-cultural values. The five pillars are development priorities and development towards one icon, namely Ambon City of Music "Music Tourism". To realize Ambon City of Music "Music Tourism", it is necessary to design a Music Tourism Area as a development priority and development of the five pillars that have been planned by the Ambon city government and the Indonesian creative economy agency. The design of this music tourism area will use symbiotic architecture as a design approach. Symbiotic architecture is expected to combine the diversity of functions that exist in this design so that it can form a complex area